Design by Advanced Elastic Analysis: An Investigation of Beam-Columns - Wang, Yunfei; Ziemian, Ronald D. (Engineering Journal, 2021)
At the heart of the provisions for assessing structural stability within the AISC Specification for Structural Steel Buildings is the direct analysis method. The fundamental concept for this method is that the more behavior is explicitly modeled within the analysis, the simpler it is to define the AISC Specification design requirements. In other words, the direct analysis method consists of calculating strength demands and available strengths according to a range of well-defined and fairly detailed analysis requirements. This paper begins with an overview of two logical extensions to AISC’s direct analysis method, both of which are now provided in AISC Specification Appendix 1, Design by Advanced Analysis. In establishing these approaches, many systems were investigated in previous research, and it was noted that systems with beam-columns subject to minor-axis bending may deserve additional attention. This paper presents a detailed study that investigates such members, as well as members subject to major-axis bending.